The ebbs and flows of the Holocaust and the Gulag memory in EU-rope. Memory dynamics in national and transnational contexts - Zessin-Jurek, Lidia (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In spring 2017 the long-awaited House of European History in Brussels was opened. Its exhibition tries to tackle not only the tumultuous history of 20th-century Europe, but also the diverse cultures of memory that surround this topic. The article touches upon the problem of co-existence and mutual relationship of the two important, if not the most crucial, topics on the European mnemonic map: that of the Holocaust and that of the Gulag. The uneven and changeable development of these memory cultures has been presented in the historical perspective and analysed through the way they have functioned at the national with Poland and Germany as examples and transnational EU levels. The concluding statement encapsulates the thesis that the EU-ropean memory confl ict in its original phase, centred around Brussels, achieved its climax some years ago. Nowadays the problems of history and memory are administered mostly within the regional and, even more, national public spheres. As the focal point of European dispute, on the other hand, new — seemingly beyond historical — topics emerged. Among them is the cultural problem sparked by the mass infl ux of immigrants to Europe.
Keywords: pamięć; Holocaust; Gułag; kryzys uchodźczy; UE